EFEK LASER FOTOKOAGULASI TERHADAP TAJAM PENGLIHATAN PADA PASIEN DIABETIC RETINOPATHY DI KLINIK MATA SMEC SAMARINDA (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Diabetic Retinopathy is one of the microvascular complications of diabetes mellitus. Diabetic retinopathy is a retinal disorder in the form of microangiopathy that is progressive and often causes blindness in adulthood. Laser photocoagulation is the gold standard for treating severe Nonproliferative Diabetic Retinopathy (NPDR) and Proliferative Diabetic Retinopathy (PDR). Laser photocoagulation is performed to prevent the progression of diabetic retinopathy. This study aims to determine the effect of laser photocoagulation on visual acuity in diabetic retinopathy patients. Visual acuity was measured before and after laser photocoagulation. This research uses an analytical observational method with a cross-sectional approach. Research data was taken from medical records at the Klinik Mata SMEC Samarinda using the total sampling method. The sample for this study was diabetic retinopathy patients who had completed laser photocoagulation and had visual acuity checked during the control two weeks after laser photocoagulation and met the inclusion and exclusion criteria. Statistical analysis was carried out to determine the difference in visual acuity before and after laser photocoagulation using the Wilcoxon test. A total of 80 eye samples were obtained. From the results of the Wilcoxon test, there was no significant difference in visual acuity results before and after laser photocoagulation in diabetic retinopathy patients with a value of p = 0.294 (p> 0.05). Visual acuity stability was achieved in 48 (60%) eye samples with severe NPDR of 36 (62.1%) and PDR of 12 (54.5%). Visual acuity after laser photocoagulation is more likely to stabilize and improve rather than worsen.
Keywords: Diabetic Retinopathy; Laser Photocoagulation; Visual Acuity